A Study on Google Classroom for Mobile Edification at University level by Using AHP Model for Initial Perceptions – A Case Study of Sankalchand Patel University - Shah, Dr. Kinchit P.; Parikh, Mr. Poojan N.; Patel, Dr. Rajesh M. (The journal of contemporary issues in business and government, 2022)
In India, many online teaching platforms are being used in universities, colleges, and schools at all levels in the context of COVID-19. This research provides an online teaching platform evaluation system in order to systematically investigate the elements that influence the selection of online teaching platforms. Following a review of a series of factors that have significant influences on the selection of online teaching platforms, eight major factors are identified. Based on the Analytic Hierarchy Process, a hierarchical structure model for online teaching platform selection is constructed. Based on the questionnaire, the rank was the same with both methods for the most preferred question and the least important question, which were derived from Performance Expectancy (PE) and Use Behaviour, respectively (UB). These findings revealed that both techniques produced the same rank for the five likert scale alternatives, with "Agree" being the most important and "Strongly disagree" being the least important. In specifically, the weights of the indicators are calculated and evaluated for each layer in order to achieve the overall ranking and, as a result, the optimal scheme. The following is the order of priority for assessment indicators of online teaching platforms, according to the findings: Google Classroom is useful in this course since it is simple to use and has all of the materials that are required to participate in Google Classroom (internet, Smartphone, laptop, etc.).